Length–weight and length–length relationships of 10 small fish species from the Ganges, Bangladesh - Hossain, Md. Yeamin; Jasmine, Saleha; Md Ibrahim, Abu Hanif; Ahmed, Zoarder Faruque; Rahman, Mohammad Mustafizur; Ohtomi, Jun (Wiley-Blackwell, 2009)
This study describes the length–weight (LWR) and length– length (LLR) relationships for ten small indigenous fish species from the lower part of the Ganges, Bangladesh, namely Ailia coila, Amblypharyngodon mola, Aspidoparia morar, Clupisoma atherinoides, Eutropiichthyes vacha, Glossogobius giuris, Gudusia chapra, Lepidocephalus guntea, Mystus vittatus, and Puntius ticto. A total of 2142 specimens, representing 10 species of 5 families used for this study were caught by traditional fishing gear from March 2006 to February 2007. Standard length (SL), total length (TL) and fork length (FL) for each specimen were measured by digital slide calipers and each body weight (BW) was taken by a digital balance. The allometric coefficient b of the LWR was close to the isometric value (b = 3.001) in G. giuris, although it suggested negative allometric growth in A. coila, A. morar, C. atherinoides, E. vacha, and P. ticto, whilst positive allometric growth in rest of the species. The results further indicated that the LLRs were highly correlated (r2 >0.890; P < 0.01). To the best our knowledge, this study presented the first reference on LWR and LLR for most of the species in Bangladesh.